Association of pulse pressure with hematoma expansion in patients with spontaneous supratentorial intracerebral hemorrhage - Wang, Chao-Ying; Lai, Su-Zhen; Kang, Bao-Cai; Lin, Yi-Zhao; Cao, Chun-Juan; Huang, Xin-Bing; Wang, Jian-Qun (Frontiers in Neurology, 2024)
Objective Recent reports have demonstrated that a wider pulse pressure upon admission is correlated with heightened in-hospital mortality following spontaneous supratentorial intracerebral hemorrhage (ssICH). However, the underlying mechanism remains ambiguous. We investigated whether a wider pulse pressure was associated with hematoma expansion (HE).Methods Demographic information, clinical features, and functional outcomes of patients diagnosed with ssICH were retrospectively collected and analyzed. Multivariate logistic regression was conducted to identify independent predictors of HE. Weighted logistic regression, restricted cubic spline models, and propensity score matching (PSM) were employed to estimate the association between pulse pressure and HE.We included 234 eligible adult ssICH patients aged 60 (51-71) years, and 55.56% were male. The mean pulse pressure was 80.94 ± 23.32 mmHg. Twenty-seven patients (11.54%) developed early HE events, and 116 (49.57%) experienced a poor outcome (mRS 3-6). Wider mean pulse pressure as a continuous variable was a predictor of HE [odds ratios (OR) 1.026, 95% confidence interval (CI) 1.007-1.046, P=0.008) in multivariate analysis. We transformed pulse pressure into a dichotomous variable based on its cutoff value. After adjusting for confounding of HE variables, the occurrence of HE in patients with ssICH with wider pulse pressure levels(≥98mmHg) had 3.78 times (OR 95% CI 1.47-9.68, P=0.006) compared to those with narrower pulse pressure levels (< 98mmHg). A linear association was observed between pulse pressure and increased HE risk (P for overall=0.036, P for nonlinear=0.759). After 1:1 PSM (pulse pressure ≥ 98mmHg vs. pulse pressure < 98mmHg), the rates of HE events and poor outcome still had statistically significant in wider-pulse pressure group [HE, 12/54(23.53%) vs. 4/51[7.84%], P=0.029; poor outcome, 34/51(66.67) vs. 19/51(37.25), P=0.003]. Conclusion Widened acute pulse pressure (≥98mmHg) levels at admission are associated with increased risks of early HE and unfavorable outcomes for patients with ssICH.